2020
DOI: 10.1249/mss.0000000000002534
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Sedentary Behavior, Physical Activity, and Cardiovascular Health: MESA

Abstract: Introduction Sleep, sedentary behavior, and physical activity are each independently associated with cardiovascular health (CVH). It is unknown how substituting time in sedentary behavior with sleep or physical activity affects overall CVH. Methods Data for this analysis were taken from the Multi-Ethnic Study on Atherosclerosis Sleep Ancillary Study. Eligible participants (N = 1718) wore Actiwatch accelerometers for 24 h and had at least 3 d of valid ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 35 publications
7
35
2
1
Order By: Relevance
“…There is potent evidence for sedentary behaviors [ 31 , 32 ], sleep [ 33 , 34 , 35 ], and MVPA [ 36 , 37 , 38 ], and emerging evidence for LPA to be associated with health outcomes [ 39 , 40 ]. Moreover, the allocation of whole 24 h time is associated with health outcomes across the lifespan [ 41 , 42 , 43 ]. Therefore, collecting data on all movement behaviors, including PA performed at all intensity categories, sedentary behaviors, and sleep over a full day (24 h) may provide researchers with the best method to observe any changes in the time accumulated in other behaviors, resulting from a single or combined behavioral intervention [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is potent evidence for sedentary behaviors [ 31 , 32 ], sleep [ 33 , 34 , 35 ], and MVPA [ 36 , 37 , 38 ], and emerging evidence for LPA to be associated with health outcomes [ 39 , 40 ]. Moreover, the allocation of whole 24 h time is associated with health outcomes across the lifespan [ 41 , 42 , 43 ]. Therefore, collecting data on all movement behaviors, including PA performed at all intensity categories, sedentary behaviors, and sleep over a full day (24 h) may provide researchers with the best method to observe any changes in the time accumulated in other behaviors, resulting from a single or combined behavioral intervention [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] Similarly, an extension of sleep duration among short-duration sleepers might attenuate gains in body weight and fat mass over a 6-year follow-up, 48 and epidemiological evidence suggests that substituting 30 min of sedentary time for the equivalent time of sleep can promote weight loss. 49 In turn, other authors have failed to report a beneficial effect of sleep interventions on blood pressure or physical activity levels in individuals with sleep impairments despite improvements in sleep quality. 50,51 Further research is therefore needed to confirm the effectiveness of sleep interventions for enhancing cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of continuous positive airway pressure for the treatment of OSA might improve glucose metabolism among diabetic or obese patients 45‐47 . Similarly, an extension of sleep duration among short‐duration sleepers might attenuate gains in body weight and fat mass over a 6‐year follow‐up, 48 and epidemiological evidence suggests that substituting 30 min of sedentary time for the equivalent time of sleep can promote weight loss 49 . In turn, other authors have failed to report a beneficial effect of sleep interventions on blood pressure or physical activity levels in individuals with sleep impairments despite improvements in sleep quality 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Others studies using isotemporal substitution modeling have also supported the importance of physical activity-related behaviors for obesity and cardiovascular health. German and colleagues reported that replacing sedentary time with MVPA was associated with more desirable cardiometabolic risk profiles [37]. Additionally, Buman et al [38], reported a powerful influence of MVPA and sedentary time on disease risk biomarkers (including waist circumference as a measure of obesity).…”
Section: Health Pillars and Bmimentioning
confidence: 99%